Experimental study of heat and mass transfer phenomena during the contact heating of solid food models. (February 2015) - Cernela, J.; Heyd, B.; Keller, S.; Bailleul, J.L.; Maillard, M.N.; Bonazzi, C.; Broyart, B.
Highlights: A contact heating device was designed to operate at controlled conditions close to domestic ones. Two food models were formulated to study transfer phenomena during contact heating. During contact heating, water evaporation under the product limits its temperature rise. Abstract: Experimental measurements of temperature rises and water loss kinetics within two types of solid food models during contact heating are discussed. A contact heating device was specially designed to reproduce the operating conditions encountered during domestic pan frying. Two different solid food models were used for the experiments: (i) a non porous solid gel containing an oil-in-water emulsion without crust formation at its lower surface during heating, and (ii) a cereal batter (water with flour) which exhibited crust formation and the development of an internal porous structure during heating. Under similar heating conditions, these products displayed very different drying and thermal behaviours. The temperature of the gel emulsion never exceeded 100 °C and was independent of the heating surface temperature in the experimental range from 160 °C to 260 °C. This limitation in product temperature rise was explained by the evaporation of liquid water exuding from the product in the interstitial space between the heating surface and the product's lower surface. By contrast, a crust was formed at the lower surface of the cereal batter, reducing the drying rate of the product at this location and allowing the product to reach temperatures higher than 100 °C.